2008
DOI: 10.1017/s0954102008001272
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic response to extreme warm and cold summers in the McMurdo Dry Valleys, East Antarctica

Abstract: Abstract:The meteorological characteristics and hydrological response of an extreme warm, and cold summer in the McMurdo Dry Valleys are compared. The driver behind the warmer summer conditions was the occurrence of down-valley winds, which were not present during the colder summer. Occurrence of the summer down-valley winds coincided with lower than typical mean sea level pressure in the Ross Sea region. There was no significant difference in the amount of solar radiation received during the two summers. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 132 publications
(160 citation statements)
references
References 28 publications
3
156
1
Order By: Relevance
“…Conditions conducive to sublimation are the main limiting factors of surface melt in this environment (Hoffman et al, 2008), and the only time when significant melt events on glacier surfaces have been recorded is during prolonged "high" temperature events (e.g. Doran et al, 2008).…”
Section: Comparison Of Ablation Results With Other Studiesmentioning
confidence: 99%
“…Conditions conducive to sublimation are the main limiting factors of surface melt in this environment (Hoffman et al, 2008), and the only time when significant melt events on glacier surfaces have been recorded is during prolonged "high" temperature events (e.g. Doran et al, 2008).…”
Section: Comparison Of Ablation Results With Other Studiesmentioning
confidence: 99%
“…However, the mean data hide the seasonal variability and especially the sensitivity of the active layer that may alter hydrological and ecological conditions (Turner et al, 2009). An example is the anomalous summer conditions that have occurred in recent years in the MDVs, including the 'wet event' in December 2000 to January 2001 (Doran et al, 2008;Turner et al, 2009;Adlam et al, 2010). The other monitored regions in continental Antarctica also showed cold permafrost, with all measured mean ground temperatures below À8.38C.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite is the case for Antarctica with 100 % glacier cover and a strong relationship with air temperature. For example, Doran et al (2008) found up to 6000-fold increase in annual streamflow in a warm year compared to a cold year. For each of these regions, similar analyses as in this paper can be performed to investigate the occurrence and causing factors of snowmelt droughts and glaciermelt droughts.…”
Section: Hypothesis 1: For Each Region the Occurrence And Severity Omentioning
confidence: 99%